UNLOCKING THE ESSENCE OF LONELINESS IN THE OLDER ADULTS: AN EXPLORATION THROUGH PARTICIPATORY RESEARCH - Zemaitaityte, Irena; Pivoriene, Jolanta; Bardauskiene, Raminta; Katkoniene, Agata; Butenaite-Switkiewicz, Joana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In Lithuania's aging culture, aspects of older individuals' "loneliness" and social isolation are becoming increasingly relevant. Despite this, older adults frequently refuse to acknowledge these life's intricacies. Numerous studies indicate that older individuals link social isolation and loneliness to a life of failure and personal worthlessness. As a result, rather than finding solutions, people frequently choose to isolate themselves even more and refrain from discussing these issues with friends or family. The loneliness experienced by older people should be acknowledged, and steps to increase social inclusion will not only extend but also greatly enhance their quality of life. Participatory research was employed to conduct the study. It is a systematic study in direct cooperation with persons for whom the research question is relevant, with the aim of acting or changing something. Participatory research favours collaborative research, where researchers and interested groups actively collaborate with sharing information and expertise. The study was conducted in a care institution providing social services. Every participant in the participatory research gave their consent to participate in the study, and they were informed about its goals, methods, and use of data. They were also given the choice to leave the study at any time if they felt it was inappropriate. The study revealed that loneliness is discerned through the emotions and behaviours of older adults; an individual's loneliness is reflected in both mental and physical health. Emotions like indifference, rage, despair, boredom, needing attention, longing, and the want to speak are signs that someone is lonely. Older people sometimes openly express loneliness but loneliness can also be associated with depression. Concerning employee motivation for change, it was observed that employees displayed a keen interest in training, comprehending its necessity and benefits. Simultaneously, it was noted that some employees may exhibit passivity and a lack of motivation to embrace change and accept innovations. Therefore, the myth that older workers are less likely to change and innovate as well as to increase their knowledge and abilities has been partially validated by participatory studies.